Establishment of simultaneous analysis validation for Perilla frutescens var. acuta extract - JEON, So-Heon (2023)
In this study, the UV spectra maximum absorption wavelengths and molecular weights of major compounds 1–3 were identified in Perilla frutescens var. acuta extract using high-performance liquid chromatography (HPLC)-DAD and HPLC-MS/MS. Luteolin-7-O-diglucuronide (1), scutellarin (2), and rosmarinic acid (3) were identified, and simultaneous analysis validation was performed for quantification using HPLC-DAD. All linearities showed R2 values of 0.9993 or higher, and the limits of detection and quantification were measured in the ranges of 4.4802–5.4133 and 13.5764–16.4038 µg/mL, respectively. The relative standard deviation (RSD) values for accuracy ranged from 0.09 to 0.89%, and the recovery rates were in the range of 99.36–101.96%. The precision RSD values within the laboratory were in the range of 0.05–1.04%, and the RSD values for repeatability evaluation were below the guideline criteria of 2%. The content change of the three marker compounds within 24 h was 0.36–0.69%, confirming the chemical stability of the extract within 24 h, which was below the guideline criteria of 2.0% established by the Ministry of Food and Drug Safety guidelines. The content analysis of the extract according to ethanol concentration showed that luteolin-7-O-diglucuronide had the highest content of 302.22 µg/mL in the 0% ethanol extract, while scutellarin and rosmarinic acid showed the highest contents of 103.61 and 118.77 µg/mL, respectively, in the 60% ethanol extract.